2010
DOI: 10.1007/s00425-010-1277-8
|View full text |Cite
|
Sign up to set email alerts
|

Polyketide derivatives active against Botrytis cinerea in Gerbera hybrida

Abstract: A previously isolated cDNA molecule from Gerbera hybrida (Asteraceae) codes for a new chalcone synthase-like polyketide synthase, 2-pyrone synthase (2PS). 2PS is able to synthesise 4-hydroxy-6-methyl-2-pyrone (triacetolactone), a putative precursor for gerberin and parasorboside, two abundant glucosides in gerbera. In this study, we show that gerbera plants transformed with the gene for 2PS in an antisense orientation and unable to synthesise gerberin and parasorboside are susceptible to Botrytis cinerea infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 64 publications
0
34
0
4
Order By: Relevance
“…To proceed in the analysis of the gerberin ⁄ parasoboside pathway, a suitable VIGS reporter is yet to be identified. Gerberin and parasorboside are synthesized also in floral tissues (Koskela et al, 2011), and from this pointof-view, GCHS1 could be used for VIGS, but as it is highly similar to G2PS1, cross down-regulation may be another obstacle. In conclusion, we have shown that TRV VIGS can be implemented for assessing gene functions in gerbera.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To proceed in the analysis of the gerberin ⁄ parasoboside pathway, a suitable VIGS reporter is yet to be identified. Gerberin and parasorboside are synthesized also in floral tissues (Koskela et al, 2011), and from this pointof-view, GCHS1 could be used for VIGS, but as it is highly similar to G2PS1, cross down-regulation may be another obstacle. In conclusion, we have shown that TRV VIGS can be implemented for assessing gene functions in gerbera.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gerbera tissues are rich in many unique secondary metabolites, such as gerberin and parasorboside, which are important in protecting the plant against microbial attack and insect herbivores (Eckermann et al. , 1998; Koskela et al. , 2011; Ulla Anttila et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the degree of oxidation and saturation of the central pyran ring, flavonoids are classified into many subgroups, such as chalcones, flavones, flavonols, flavandiols, anthocyanins, and proanthocyanidins (Winkel-Shirley, 2001). Flavonoids possess significant and diverse biological functions, including protection against UV radiation, defense against phytopathogens and herbivores, regulation of auxin transport, and signaling between plants and microbes, and, importantly, they are major pigments for flowers, fruits, seeds, and leaves (Stafford, 1991;Mol et al, 1998;Winkel-Shirley, 2002;Bradshaw & Schemske, 2003;Koskela et al, 2011;Ferreyra et al, 2012;Jaakola, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that HMC is synthesized via a pentaketide (Inoue et al ., ) (Figure b), but the enzymes responsible for the synthesis are not known. HMC and aglycones of gerberin and parasorboside are involved in defense against Botrytis cinerea infection in gerbera (Koskela et al ., ). Especially HMC showed strong antifungal activity.…”
Section: Introductionmentioning
confidence: 97%